Overexpression of Cannabinoid CB2 Receptor in the Brain Induces Hyperglycaemia and a Lean Phenotype in Adult Mice - Romero-Zerbo, Silvana Yanina; Garcia-Gutierrez, M S; Suárez-Pérez, Juan; Rivera-González, Patricia; Ruz-Maldonado, Inmaculada; Vida, M.; Rodriguez-de-Fonseca, Fernando; Manzanares, Jorge; Bermúdez Silva, Francisco Javier (Blackwell Publishing Ltd, 2009)
t is well known that the endocannabinoid system, through cannabinoid CB1 receptor activation,has an important role in the main aspects of energy balance (i.e. food intake, energy expenditureand glucose and fat metabolism), orchestrating all the machinery involved in body weight con-trol and energy homeostasis. A number of studies have revealed a crucial role of brain CB1receptors in these processes. However, functional cannabinoid CB2 receptors have also beendescribed in the brain, with no studies addressing their putative role in body weight control andglucose homeostasis. We have tested this hypothesis by analysing fasting-induced feeding, bodyweight, some hypothalamic neuropeptides, glucose tolerance and plasma hormones in an animalmodel speciﬁcally overexpressing CB2 receptors in the central nervous system. We found thatspeciﬁc overexpression of CB2 receptors in the brain promoted higher basal glucose levels,decreased fasting-induced feeding and, eventually, led to a lean phenotype and glucose intoler-ance. These ﬁndings could not be attributed to decreased locomotor activity, increased anxietyor depressive-like behaviours. The expression of relevant neuropeptides such as pro-opiomelano-cortin and galanin in the arcuate nucleus of the hypothalamus was altered but not those of theCB1 receptor. Indeed, no changes in CB1 expression were found in the liver, skeletal muscle andadipose tissue. However, cannabinoid CB1 and CB2 receptor expression in the endocrine pan-creas and glucagon plasma levels were decreased. No changes in plasma adiponectin, leptin,insulin and somatostatin were found. Taken together, these results suggest a role for centralcannabinoid CB2 receptors in body weight control and glucose homeostasis.
Keywords: Diabetes; Cnr2; CNS; Glucose homeostasis; Body weight